2016
DOI: 10.1590/1678-4162-8150
|View full text |Cite
|
Sign up to set email alerts
|

Description of Methicillin-resistant Staphylococcus pseudintermedius from canine pyoderma in Minas Gerais state, Brazil

Abstract: Methicillin-resistant Staphylococcus pseudintermedius (MRSP) is of worldwide concern in veterinary medicine. The identification of resistant strains is necessary for proper treatment and the prevention of its propagation among animals. This study aimed to identify S. pseudintermedius isolated from canine pyoderma and evaluate their resistance profiles. Lesions from 25 dogs with pyoderma were sampled. Bacterial isolates were subjected to phenotypic and genotypic analysis for identification of the causative agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…Here, resistance to oxacillin by disk diffusion was detected in 13 of 44 strains (29,55%). However, PCR analysis for mecA revealed that seven out of the 13 strains classified as resistant to oxacillin by disk diffusion harbored the mecA gene and five strains that were positive for mecA (ELHASSAN et al, 2015;BOURGUIGNON et al, 2016). Although, mecA seems to be the most common gene associated with meticillin resistance in S. pseudintermedius, some studies have shown that another gene (mecC) could also be responsible for this resistance profile (KJELLMAN et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, resistance to oxacillin by disk diffusion was detected in 13 of 44 strains (29,55%). However, PCR analysis for mecA revealed that seven out of the 13 strains classified as resistant to oxacillin by disk diffusion harbored the mecA gene and five strains that were positive for mecA (ELHASSAN et al, 2015;BOURGUIGNON et al, 2016). Although, mecA seems to be the most common gene associated with meticillin resistance in S. pseudintermedius, some studies have shown that another gene (mecC) could also be responsible for this resistance profile (KJELLMAN et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Amplicons were separated by electrophoresis on a 1.5% agarose gel with a 1-kb molecular marker (ThermoScientific ® Waltham, Massachusetts, USA). S. pseudintermedius MRSP 3279, a reference strain previously used in other studies (BANNOEHR et al, 2009;BOURGUIGNON et al, 2016) were used as positive controls and amplification of sterile water served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…En el pioderma canino, Staphylococcus intermedius (pseudintermedius) es la bacteria más frecuente ( No es frecuente la prescripción de estudios microbiológicos para el abordaje clínico del pioderma canino (Hensel et al, 2015;Guardabassi et al, 2017), por lo que el diseño de la antibioticoterapia es de carácter empírico, basado en los fármacos con conocida eficacia sobre los estafilococos; empero, se corre el riesgo de utilizar aquellos que favorezcan la resistencia, de allí que la implementación de esta herramienta diagnóstica es recomendable en casos particulares (Cain, 2013;Hensel et al, 2015;Guardabassi et al, 2017). Por otro lado, la respuesta a los tratamientos varía especialmente cuando en el proceso infeccioso están involucradas cepas resistentes a la meticilina como las de Staphylococcus aureus (SARM) y S. pseudintermedius (SPRM), de las cuales ya se tienen reportes de afecciones en animales (Morris et al, 2006; Van Duijkeren et al, 2011; Frank y Loeffler, 2012; Beça et al, 2015), incluyendo dermatitis en caninos con resistencia a penicilina (Antúnez et al, 2009), meticilina (Bourguignon et al, 2016) y hasta multirresistentes (Abusleme, 2009; dos Santos et al, 2016), por lo que la generación de información adecuada a los contextos espacio-temporales sería de utilidad para orientar a los practicantes de la clínica veterinaria en pequeños animales.…”
Section: Introductionunclassified
“…Entretanto, essas bactérias parecem ter um papel oportunista, uma vez que têm sido identificadas em casos de otite externa, piodermites, infecções do trato urinário, assim como o observado neste estudo, além de complicações pós-cirúrgicas[27,29,32].Diversos estudos descrevem as bactérias do gênero Staphylococcus como as mais isoladas da pele e orelhas por constituírem parte da microbiota residente destes locais[31]. O gênero tem sido identificado como o mais importante nos casos de ITUs nos cães[5,29,[39][40][41][42][43][44][45], fato este observado também no presente estudo. em associação ou não ao clavulanato de potássio e a cefalexina são também consideradas drogas de eleição[24].…”
unclassified